Evaluation of Students’ Attitudes and Science Process Skills toward Middle School Science Subject in Indonesia - Ernawati, Margaret Dwi Wiwik; Asrial, Asrial; Perdana, Rahmat; Septi, Sabila Eka; Rahmi, Rahmi (Jurnal Pendidikan Progresif, 2021)
Evaluation of Students’ Attitudes and Science Process Skills toward Middle School Science Subject in Indonesia. Objective: This research aims to determine the differences and the relationship between attitudes and science process skills in science learning in Batanghari Regency, namely Junior High School 34 Batanghari and Junior High School 35 Batanghari. Method: Quantitative method with associative and comparative type. The instrument in this study used a questionnaire for attitudes and an observation sheet for science process skills. Quantitative data analysis technique used random sampling with 140 students as respondents. Findings: Based on the t-test obtained sig.(2 tailed) 0.048, 0.047, 0.039, 0.038 < 0.05, so there are differences in students’ attitudes and science process skills. From the correlation test obtained sig. (2-tailed) of 0.035 and 0.037 < 0.05 which indicated the relationship between attitudes and science process skills. Conclusion: Differences and the relationship between students’ attitudes and science process skills in science learning at Junior High School 34 Batanghari and Junior High School 35 Batanghari. Keywords: evaluation, attitude, science process skills DOI: 10.23960/jpp.v11.i2.202110